2014
DOI: 10.1055/s-0034-1384815
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in the Prevention of Benign Paroxysmal Positional Vertigo: Probable Association

Abstract: Introduction Physical inactivity is an important risk factor for many age-related diseases and symptoms such as dizziness and vertigo. Objective The aim of the study was to investigate the possible association between benign paroxysmal positional vertigo (BPPV) and regular physical activity in elderly subjects. Methods This cross-sectional study included 491 elderly individuals who lived independently. Physical exercise was assessed through a questionnaire and BPPV by history and the Dix-Hallpike maneuver. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Our analysis showed no significant association between BPPV and physical inactivity. However, previous studies showed that moderate physical exercise can prevent the occurrence of BPPV and decrease the risk of falls and fractures, especially in the elderly (46). Intense physical activity may trigger posttraumatic BPPV without head trauma (47), but a study showed that BPPV caused by intense physical activity was a rare condition (48).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis showed no significant association between BPPV and physical inactivity. However, previous studies showed that moderate physical exercise can prevent the occurrence of BPPV and decrease the risk of falls and fractures, especially in the elderly (46). Intense physical activity may trigger posttraumatic BPPV without head trauma (47), but a study showed that BPPV caused by intense physical activity was a rare condition (48).…”
Section: Discussionmentioning
confidence: 99%
“…42 A recent cross-sectional study that included 491 elderly participants confirmed there is an association between BPPV and lack of physical activity in women. 43 Thus, sedentary elderly people present more dizziness than those who practice some type of physical activity. 42 In the present study, over half of the elderly people did not perform any physical activity and, among those who did, walking was the most common.…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted in South Korea, however, involvement of other semicircular canals (not just the PC) has been shown to be more common than previously reported in western countries [25]. Even though the PC was most commonly involved (59-61%), BPPV of the non-pure PC-BPPV type comprises about 40% of total BPPV, especially with involvement of the horizontal canal (HC-BPPV), where the otolithic debris may be located either in the canal (canalolithiatic or geotropic, 61-66%) or attached to the cupula (cupulolithiatic or apogeotropic, 31-33%) [10,21]. The causes for this discrepancy is unknown [25].…”
Section: Clinical Featuresmentioning
confidence: 97%
“…Indeed, a recent meta-analysis found that female gender, hypertension, diabetes mellitus, hyperlipidemia, osteoporosis, and vitamin D deficiency are risk factors for recurrences of BPPV [19]. Linked to this is the finding that elderly women with a lack of physical activity have a 2.6 times higher risk for BPPV than those who undertake regular activity [21]. Furthermore, vitamin D deficiency (< 10 ng/ ml) and insufficiency (10-20 ng/ml) have been associated with BPPV with an odds ratios of 3.8 and 23.0 [22].…”
Section: Pathophysiologymentioning
confidence: 99%